2017
DOI: 10.1016/s1473-3099(17)30480-2
|View full text |Cite
|
Sign up to set email alerts
|

Spreading the knowledge on the epidemiology of sepsis

Abstract: Notwithstanding the definition we choose, sepsis-associated short-term and long-term mortality and morbidity remain a major public health concern. From a high-income country perspective, the half-full glass (as shown by a sustained decline in mortality 1,2 ) is counterbalanced by the half-empty glass in which the high burden of long-term cognitive and functional decline seen in survivors of long-term sepsis 3 is increasingly recognised. However, in low-income and middle-income countries, the growing evidence b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…WHO with partners has highlighted the importance of compassionate and good QoC at facility level [39]. In many LMIC, there is often a significant variation in the existing quality of care, with some hospitals providing excellent care but with many others having neither the required skills, supplies nor the motivation, resulting in poorer quality care including inadequate pain management [40].…”
Section: Discussionmentioning
confidence: 99%
“…WHO with partners has highlighted the importance of compassionate and good QoC at facility level [39]. In many LMIC, there is often a significant variation in the existing quality of care, with some hospitals providing excellent care but with many others having neither the required skills, supplies nor the motivation, resulting in poorer quality care including inadequate pain management [40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors found that the use of low tidal volumes (<8mL/kg predicted weight) was similar in MICs and HICs (42•4% vs 44•2%; absolute difference -1•69% [95% CI -9•58 to 6•11]; p=0•67), as were most ventilatory parameters (except for a small decrease in positive end expiratory pressure in the ICUs in MICs than in HICs (5 [IQR 5-8] vs 6 [5][6][7][8] cm H2O; p=0•0011). However, ICU mortality was much greater in MICs than in HICs (30•5% vs 19•9%; p=0•0004; adjusted effect 16•41% [95% CI 9•52-23•52]; p<0•0001).…”
mentioning
confidence: 98%
“…Some of these factors have already been shown in previous analyses in MIC hospitals: worse outpatient health care, fewer (and perhaps lesser qualified) health professionals (particularly nursing), greater number of comorbidities, and lower availability of hospital and ICU beds (thus selecting patients with more severe conditions and more advanced clinical conditions). 6 , 7 , 8 All of these factors are probably related to socioeconomic conditions per se, perhaps more than to the ventilatory strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jorge I. F. Salluh 1,2* , Thiago Lisboa 3,4 and Fernando A. Bozza 1,5 Background The delivery of critical care is a major challenge for developing countries [1]. The inequity of access to an ICU bed, heterogeneous triage policies, a low staff/patient ratio and suboptimal adherence to evidence-based practices contribute to disproportionally high mortality of sepsis and acute respiratory distress syndrome in these countries [2][3][4][5]. In addition, limited step-down and specialized ward beds' availability further widens the gap between critical and non-critical care inside hospitals.…”
mentioning
confidence: 99%